The overuse of intrapartum cardiotocography (CTG) for low-risk women: An actor-network theory analysis of data from focus groups. Issue 6 (November 2022) - Jepsen, Ingrid; Blix, Ellen; Cooke, Helen; Adrian, Stine W.; Maude, Robyn
Abstract: Background: There is an overuse of cardiotocography for intrapartum fetal monitoring for low-risk women in high-income countries, despite recommendations from evidence-based guidelines. Aim: To understand why midwives use cardiotocography for low-risk women despite evidence-based recommendations and to understand the roles of the cardiotocograph machine. Method: This qualitative study used focus groups for data collection. Thirty-one midwives and three student midwives participated from four different countries: New Zealand, Australia, Denmark, and Norway. Constant comparative analysis, informed by an actor-network theory framework, was the method of data analysis. Findings: Cardiotocography was multifaceted and influenced all attendants in the birth environment. The cardiotocograph itself is assigned different roles within the complex networks surrounding childbirth. The cardiotocograph's roles were as a babysitter, the midwives' partner, an agent of shared responsibility, a protector that 'covers your back', a disturber of normal birth, and a requested guest. Discussion: The application of the actor-network theory enabled us to understand how midwives perceive cardiotocography. The assigned roles of the cardiotocograph shape its everyday use more than evidence-based guidelines. Discussion of these inconsistencies must inform the use of cardiotocography in the care of women with low-risk pregnancies. Conclusion: We found that the cardiotocograph is a multifaceted actant that influences practice by performing different roles. Drawing on this study, we suggest that actor-network theory could be a helpful theoretical perspective to critically reflect upon the increasing use of technologies within maternity care.